Ascetic Passions : Emotions in Early Christian Egypt - Crislip, Andrew, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
Ascetic Passions: Emotions in Early Christian Egypt reveals the role of emotions in shaping early Christian theology, community, and monastic practices in Egypt. Drawing from biblical interpretation, theological treatises, and Coptic monastic and apocryphal literature, Crislip explores how emotions such as envy, anger, sadness, and joy influenced Christian life and thought. The book highlights how early Christians saw emotions as both spiritual challenges and tools for moral growth. Discussions of figures like Evagrius of Pontus and Shenoute showcase how emotional regulation, community, and identity were central to monastic life. The volume offers new insights into the emotional landscape of late antiquity.